2018
DOI: 10.1002/jsfa.9186
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultrasonication, agitation and stirring extraction techniques on the physicochemical properties, health‐promoting phytochemicals and structure of cold‐brewed coffee

Abstract: The combination of ultrasonication and agitation might be the best option to enhance the various phytochemicals in cold-brewed coffee. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 31 publications
4
24
0
Order By: Relevance
“…This shows that ultrasound-assisted extraction is more efficient in extracting antioxidant compounds than the conventional method. Similar trend was reported for the ultrasound-assisted extraction of cold-brewed coffee ( 37 ) and Origanum majorana leaves ( 26 ).…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…This shows that ultrasound-assisted extraction is more efficient in extracting antioxidant compounds than the conventional method. Similar trend was reported for the ultrasound-assisted extraction of cold-brewed coffee ( 37 ) and Origanum majorana leaves ( 26 ).…”
Section: Resultssupporting
confidence: 83%
“…The same trend was also reported by Ahmed et al . ( 37 ) for cold-brewed coffee extracts, which might be due to the stronger tendency of ABTS radicals to donate electron than of the DPPH radical.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The study of optimizing the traditional method of cold brewing showed that agitation greatly improved the caffeine extraction. Agitation causes tissue and cell wall disruption, facilitating the transfer of more soluble solids and caffeine through the cell membrane to the solution 21 . In Fig.…”
Section: Resultsmentioning
confidence: 99%